Analisis Rasio Likuiditas Untuk Mengukur Kemampuan Perusahaan Dalam Membiayai Aktivitas Perusahaan : Studi Kasus Pada PDAM Tirta Pakuan, Bogor. - Muktiadji, Nusa; Trisnawati, Dini (Sekolah Tinggi Ilmu Ekonomi Kesatuan, 2008)
The goal of this research is to find out liquidity ratio analysis of a company, its activities, and how to finance its activities. The researchers utilize descriptive analysis method, that is research of of matters in the form of facts of a population. Data analysis technique used here is ratio analysis, and liquidity ratio is smooth ratio, fast ratio, and cash ratio on smooth ratio. Activity ratio used here is rotation ratio of commerce debt, rotation ratio of total assets, and rotation of work capital. The outcome of this research shows that the company, in carrying out its activities during 2002 â 2005, got increase on commerce debt rotation, but smooth debt increased as well caused by interest of long term debt which had been overdue. And overall, during 2002 â 2005 its performance was good, except its stock rotation got decrease. The analysis result shows that the company in carrying out its activities must be accelerated to compensate for long term debt that had been overdue and the company has to increase its selling by looking for new customers and new spring source. Keywords: Liquidity ratio; Financing activities